2002
DOI: 10.1161/01.cir.0000027817.55925.b4
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of Thioredoxin-1 in Transgenic Mice Attenuates Adriamycin-Induced Cardiotoxicity

Abstract: Background-Adriamycin (ADR) is an anticancer drug known to cause severe cardiac toxicity by generating free radicals.We investigated the role of a redox-regulating molecule, thioredoxin-1 (TRX1), in ADR-induced cardiotoxicity. Methods and Results-The in vitro study showed that TRX1 was dose-dependently increased concomitant with the formation of hydroxyl radicals in ADR-treated neonatal rat cardiomyocytes. Lactate dehydrogenase-releasing assay showed that treatment with recombinant human TRX1 suppressed cardio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
116
0
2

Year Published

2006
2006
2024
2024

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 185 publications
(123 citation statements)
references
References 21 publications
(23 reference statements)
5
116
0
2
Order By: Relevance
“…Expression of catalase in mitochondria increased longevity in transgenic mice (154). Decreased Trx-2 in hemizygous Trx-2 ϩ/Ϫ mice had increased sensitivity to oxidants (141), and Trx-1 transgenic mice were protected against cardiotoxicity from doxorubicin (159). Gpx1 knockout mice demonstrated increased susceptibility to H 2 O 2 (36).…”
Section: Oxidative Stress As a Disruption Of Redox Signaling And Controlmentioning
confidence: 99%
“…Expression of catalase in mitochondria increased longevity in transgenic mice (154). Decreased Trx-2 in hemizygous Trx-2 ϩ/Ϫ mice had increased sensitivity to oxidants (141), and Trx-1 transgenic mice were protected against cardiotoxicity from doxorubicin (159). Gpx1 knockout mice demonstrated increased susceptibility to H 2 O 2 (36).…”
Section: Oxidative Stress As a Disruption Of Redox Signaling And Controlmentioning
confidence: 99%
“…TRX is a 12 kDa protein with a highly conserved redox-active dithiol/disulfide active site sequence, Cys 32 -Gly-Pro-Cys 35 , which, together with GSH constitutes the major redox-regulating molecules that maintain cellular redox balance [16,17]. Several studies have demonstrated protective effect of TRX in diseases associated with increased oxidative stress such as post-ischaemic reperfusion injury, adriamycin-induced cardiotoxicity and diabetic nephropathy [18][19][20][21]. Additionally, while elevated serum levels of TRX are seen in patients with acute asthma exacerbations [22], the administration of exogenous TRX suppress AHR and airway inflammation in a murine model of asthma [23].…”
Section: Introductionmentioning
confidence: 99%
“…Thioredoxin-1 (Trx) and glutaredoxin-1 (Grx) are members of this superfamily that function within the cytoplasm to detoxify hydroperoxides and to maintain protein thiols in a normally reduced state [2,6]. A different pair of functionally related enzymes is also localized to the mitochondria [7].…”
Section: Introductionmentioning
confidence: 99%